Desain Sistem Manufaktur Menggunakan ERP System: Suatu Pendekatan Praktis - Vincent Gaspersz (Jurnal Siasat Bisnis, 2001)
One of the manufacturing management systems that have been known internationally is Enterprise Resource Planning (ERP), but many people have not yet known about the ERP methodology and its application within manufacturing organizations. This article provides in-depth knowledge of the ERP methodology and its application in manufacturing organizations. This article can be a useful reference for both manufacturing business scientists and practitioners or anyone who seeks for information on the implementation of ERP system in manufacturing organization. Key words: Enterprise Resource Planning (ERP) System, manufacturing system